Prospective of Bosnia and Herzegovina - Mašić Alma (Temida)
In this paper current truth and reconciliation initiatives in Bosnia and Herzegovina are reviewed, with special emphasis on the activities of ICMP. Within the scope of its activities, ICMP has launched the implementation of the project "Paths to reconciliation", which is intended for the associations of the families of missing persons in the area of the former Yugoslavia. This project enables the missing families’ associations to confront themselves within their national environments through a series of workshops, before tackling the difficult and painful issues that burden every ethnic community. This project also opens the possibility to explore various options that will ensure the implementation of justice and open space for a dialog between victim groups on the regional and international level and to encourage the exchange of experiences in searching for the truth and building trust. In the future, better coordination of all activities and initiatives concerning the confrontation with the past ought to be established. Such initiatives should provide a place and space for war victims groups, other NGO-s and other segments of the civic society to give their recommendations for the resolution of their common problems and for further activities in this process.